A rights-based approach for right to education in Nigeria (2014)
The focal point of this paper is the application of rights-based approach (RBA) programming the right to education in Nigeria. It describes RBA in terms of the State’s obligation so to respond to fulfilling the right of the child to education. This approach is most essential for realising the right to education in developing countries including Nigeria, as it identifies the state as the duty bearer and the children as the right holders. The State therefore is held accountable for the implementation of the right and children are entitled to claim the right to free primary education. The paper distinguishes RBA from 'needs-based approach’ explaining that the latter is often met out of charitable intentions, whereas the rights-based approach is based on legal obligations that the state must fulfil. It has explored the important issue of education delivery in Nigeria from within human rights perspective. Also, it is aimed through this paper to deepen our understanding of the constituent elements in a RBA programming, such as indivisibility, empowerment, equality and accountability. In essence, the paper has provided an insight into some steps that need to be taken for the right to education in Nigeria to have a . * significant impact on both policy and practical outcomes in Nigeria